ChemInform Abstract: New Insights into Ordering and Dynamics in Organic Ionic Plastic Crystal Electrolytes. Issue 27 (16th June 2016) - Forsyth, M.; Chen, F.; O'Dell, L. A.; Romanenko, K.
Abstract: Review: 39 refs.